PEMERIKSAAN KESEHATAN GRATIS DALAM UPAYA PENINGKATAN KESADARAN MASYARAKAT TERHADAP DETEKSI DINI PENYAKIT TIDAK MENULAR DI DESA AMPALU KOTA PARIAMAN - Linda Marni; Kheniva Diah Anggita; Armaita Armaita; Prima Yoselina (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Non-communicable diseases (NCDs) are chronic diseases and are not transmitted from person to person. The prevalence of NCDs continues to increase along with changes in people's lifestyles in an unbalanced direction. Based on WHO data in 2017, NCDs are one of the causes of the most deaths, which is 69.9% of the total disease burden in Indonesia. The importance of routine health checks is a preventive step in detecting health problems early and maintaining the quality of life in the community. The purpose of this activity is to conduct public health checks in an effort to increase public awareness of the early detection of non-communicable diseases in the people of Ampalu village, Pariaman City. NCD risk control can be applied with CERDIK behavior, namely periodic health checks, eliminating cigarette smoke, diligent physical activity, a healthy diet with balanced calories, adequate rest, and stress control. This behavior is a healthy behavior that is easy to remember and apply in daily life so that we can maintain body health, improve fitness, and enjoy old age without the burden of disease The method of activities carried out is in the form of discussions and direct practice of health checks for blood pressure, cholesterol, blood glucose, uric acid and calculation of the Body Mass Index (BMI). This community service is carried out by nursing lecturers at the Padang State University Clinic in Pariaman. The overall health examination results were quite good with the average normal examination results.